The Expulsion of Jews from Iraq, 20th Century : The Agonies of Redemption - Yehuda, Zvi (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2025)
The Expulsion of Jews from Iraq, 20th century , tells the story of Jews who were persecuted and murdered by nationalist Iraqi regimes from 1932-1952. It details firings, school expulsions, show trials and confiscation of assets while Israel, Britain, the USA and France ignored pleas for help. Yehuda's book includes the Israeli intelligence network's pre- and post-independence activity in Iraq, rare evidence gathered by the author from newly available Iraqi archives, archival Israeli agency reports, interviews the author had with Iraqi Jews who immigrated to Israel, among others. It presents the definitive story of the Masuda Shemtob Synagogue bombing and fills important gaps concerning the Great Powers' relations with Iraq during the Israeli-Arab conflict. See Less